Waterloo Handedness Questionnaire: Cross-Cultural Adaptation and Psychometric Properties of the Arabic Version - Saleh M. Aloraini (Occupational Therapy International)
Handedness is one of the most studied behavioural predictors of cerebral lateralization. Assessing handedness is often essential in neuropsychology and motor behaviour research. Thus, it is important that self-reported assessment tools for determining handedness are available in multiple languages for different cultures. The purpose of the present study was to conduct a translation and cross-cultural adaptation of the Waterloo Handedness Questionnaire into the Arabic language and to assess its psychometric properties. Two independent forward translations were performed by two native Arabic speakers and then synthesized into one version. The synthesized version was backtranslated into English by two independent bilingual translators. An expert committee was formed to review the translation and adaptation process. A final Arabic version of the WHQ was obtained, the WHQ-Ar. Two hundred and ninety adult Arabic speakers were recruited to participate in the study and investigate the properties of the WHQ-Ar. Results showed that the WHQ-Ar had no floor or ceiling effect. For construct validity, results of factor analysis revealed that the WHQ-Ar had two dimensions. Further, the WHQ-Ar had excellent internal consistency with Cronbach’s alpha=0.93. For test-retest reliability, intraclass correlation coefficient score was 0.94. The Bland-Altman plot showed acceptable agreement between test and retest scores. Therefore, the WHQ-Ar is a valid, reliable tool and ready for use among the Arabic-speaking population for determining handedness.